Complex Interplay Between COVID-19 Lockdown and Myopic Progression - Cai, Tao; Zhao, Lianghui; Kong, Ling; Du, Xianli (Frontiers in Medicine, 2022)
Purpose: To compare the myopic progression before and during strict home confinement when coronavirus disease 2019 (COVID-19) outbreak and explore the potential influencing factors. Methods: A cross-sectional study. 115 myopic children (115 right eyes) who replace their frame-glasses from December 2019 to January 2020 and with complete refractive records in our hospital since myopia were involved in the study. At the beginning of the strict home confinement and after a 3-month strict home confinement during the COVID-19 pandemic, they were invited to our hospital to examine the axial length and refractive errors. And visual functions, convergence insufficiency symptom survey (CISS) scale and questionnaires were also performed. Besides, the axial lengths and refractive errors before the COVID-19 were got from outpatient case files. The effect of strict home confinement on myopia was assessed by comparing monthly axial elongation before COVID-19 and during strict home confinement. Spearman correlation analysis was performed to explore the correlation between potential influencing factors and myopia progression. Results: Axial length’s monthly elongation during strict home confinement was 35% higher than normal periods (0.046 vs. 0.033 mm/month, P=0.003). The proportion of severe asthenopia doubled (P=0.020). For myopia progression, heredity, close indoor work time and electronic products were risk factors. Besides, the protective factors were age, rest time after continuous eye usage, sleep time and distance from eye to computer screen. Conclusions: During COVID-19, the decline in outdoor activities and increase of exposure time to digital screens accelerated the progression of myopia by 1/3.